Attention, cognitive control and motivation in ADHD: Linking event-related brain potentials and DNA methylation patterns in boys at early school age - Heinrich, Hartmut; Grunitz, Juliane; Stonawski, Valeska; Frey, Silke; Wahl, Simone; Albrecht, Bjoern; Goecke, Tamme W.; Beckmann, Matthias; Kornhuber, Johannes; Fasching, Peter; Moll, Gunther; Eichler, Anna (Scientific Reports, 2017)
In order to better understand the underpinnings of attention-deficit/hyperactivity disorder (ADHD), we targeted the relationship of attentional, cognitive control and motivational processes with DNA methylation patterns of 60 candidate genes in boys at early school age. Participants (6 to 8 years; N = 82) were selected from a German longitudinal cohort (FRANCES). ADHD-related behaviour was assessed via maternal ratings. Performance and event-related potential measures (inter alia Cue-P3 and Nogo-P3), which were recorded in a motivational go/nogo task, indicated diminished attentional orienting, reduced inhibitory response control and a larger motivational effect on performance in ADHD already at this relatively young age. Methylation patterns were analysed in buccal cell DNA with the Illumina HumanMethylation 450K array. For CpG sites at genes of the dopaminergic (COMT, ANKK1) and the neurotrophic (BDNF, NGFR) system, associations with the Nogo-P3 as well as ADHD symptom severity were found suggesting that these systems are involved in response control deficits in ADHD. Methylation effects related to both functional aspects and ADHD behaviour were also observed for DPP10 and TPH2. Epigenetic mechanisms may play a role in ADHD-associated deficits but findings need to be replicated in larger samples and are limited by the fact that only peripheral methylation could be considered.
EVALuna2:33560

Blockade of IL-36 Receptor Signaling Does Not Prevent from TNF-Induced Arthritis - Derer, Anja; Groetsch, Bettina; Harre, Ulrike; Böhm, Christina; Towne, Jennifer; Schett, Georg; Frey, Silke; Hueber, Axel (PLoS ONE, 2014)
Interleukin (IL)-36? is a newly described member of the IL-1 cytokine family with a known inflammatory and pathogenic function in psoriasis. Recently, we could demonstrate that the receptor (IL-36R), its ligand IL-36? and its antagonist IL-36Ra are expressed in synovial tissue of arthritis patients. Furthermore, IL-36? induces MAP-kinase and NF?B signaling in human synovial fibroblasts with subsequent expression and secretion of pro-inflammatory cytokines.To understand the pathomechanism of IL-36 dependent inflammation, we investigated the biological impact of IL-36? signaling in the hTNFtg mouse. Also the impact on osteoclastogenesis by IL-36? was tested in murine and human osteoclast assays.Diseased mice showed an increased expression of IL-36R and IL-36? in inflamed knee joints compared to wildtype controls. However, preventively treating mice with an IL-36R blocking antibody led to no changes in clinical onset and pattern of disease. Furthermore, blockade of IL-36 signaling did not change histological signs of TNF-induced arthritis. Additionally, no alteration on bone homeostasis was observed in ex vivo murine and human osteoclast differentiation assays.Thus we conclude that IL-36? does not affect the development of inflammatory arthriti
EVALuna2:12991

Effects of In utero environment and maternal behavior on neuroendocrine and behavioral alterations in a mouse model of prenatal trauma - Golub, Yulia; Canneva, F.; Funke, R.; Frey, Silke; Distler, Jörg; von Hörsten, Stephan; Freitag, C. M.; Kratz, Oliver; Moll, Gunther; Solati, Jalal (Developmental Neurobiology, 2016)
Maternal posttraumatic stress disorder (PTSD) following trauma exposure during pregnancy is associated with an increased risk of affective disorders in children. To investigate the mechanisms by which prenatal trauma and/or maternal PTSD affect brain development and behavior we established a mouse model of prenatal traumatic (PT) experience based on the application of an electric foot shock to C57Bl/6N female mice on the gestational day 12 during their pregnancy. The model is based on a previously validated animal model of PTSD. We found high anxiety levels and poor maternal care along with reduced serum prolactin and increased corticosterone levels in dams following maternal trauma (MT). PT-pups were born smaller and stayed smaller throughout their life. We show increased time and frequency of ultrasonic calls in PT-pups when separated from the mothers on the postnatal day (PND) 9. Cross-fostering experiments reveal lower anxiety levels in PT pups raised by healthy mothers as compared to trauma-naive pups raised by MT-dams. Importantly, the combination of prenatal trauma and being raised by a traumatized mother leads to: (1) the highest corticosterone levels in pups, (2) longest USV-call time and (3) highest anxiety levels in comparison to other experimental groups. Our data indicates a distinct change in maternal care following MT which is possibly associated with trauma-induced decrease in prolactin levels. Furthermore, we show that maternal behavior is crucial for the development of the offspring anxiety and specific aspects in maternal care overwrite to a significant extend the effects of in utero and postnatal environment. © 2016 Wiley Periodicals, Inc. Develop Neurobiol 76: 1254-1265, 2016.
EVALuna2:13269

Eosinophils preserve bone homeostasis by inhibiting excessive osteoclast formation and activity via eosinophil peroxidase. - Andreev, Darja; Kachler, Katerina; Liu, Mengdan; Chen, Zhu; Krishnacoumar, Brenda; Ringer, Mark; Frey, Silke; Krönke, Gerhard; Vöhringer, David; Schett, Georg; Bozec, Aline (Nature Communications, 2024)
Eosinophils are involved in tissue homeostasis. Herein, we unveiled eosinophils as important regulators of bone homeostasis. Eosinophils are localized in proximity to bone-resorbing osteoclasts in the bone marrow. The absence of eosinophils in ΔdblGATA mice results in lower bone mass under steady-state conditions and amplified bone loss upon sex hormone deprivation and inflammatory arthritis. Conversely, increased numbers of eosinophils in IL-5 transgenic mice enhance bone mass under steady-state conditions and protect from hormone- and inflammation- mediated bone loss. Eosinophils strongly inhibit the differentiation and demineralization activity of osteoclasts and lead to profound changes in the transcriptional profile of osteoclasts. This osteoclast-suppressive effect of eosinophils is based on the release of eosinophil peroxidase causing impaired reactive oxygen species and mitogen-activated protein kinase induction in osteoclast precursors. In humans, the number and the activity of eosinophils correlates with bone mass in healthy participants and rheumatoid arthritis patients. Taken together, experimental and human data indicate a regulatory function of eosinophils on bone.
EVALuna2:554518

Epigenetic modifications in children associated with maternal emotional stress during pregnancy - Stonawski, Valeska; Frey, Silke; Golub, Yulia; Moll, Gunther; Heinrich, Hartmut; Eichler, Anna (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2018)
Besides typical physical and hormonal changes during pregnancy, this life period is often associated with an increased emotional and mental stress for women. For the child, the time in utero is regarded as a critical developmental period since adverse stimuli during pregnancy can have lasting consequences for the fetal and postnatal health and development. Thus, prenatal depression, anxiety and stress are considered as risk factors for developmental delay, emotional and behavioral problems. Epigenetic modifications, especially modifications in DNA methylation, are discussed as a possible biological mechanism that could explain the association between prenatal emotional stress and altered developmental and health outcomes of the child. This review summarizes evidence for DNA methylation changes related to prenatal emotional stress from studies with a candidate-gene approach as well as epigenome-wide association studies. Problematic issues are discussed and recommendations for future research are presented.
EVALuna2:36372

Full Length Interleukin 33 Aggravates Radiation-Induced Skin Reaction - Kurow, Olga; Frey, Benjamin; Schuster, Louis; Schmitt, Verena; Adam, Susanne; Hahn, Madelaine; Gilchrist, Derek; Mcinnes, Iain B.; Wirtz, Stefan; Gaipl, Udo; Krönke, Gerhard; Schett, Georg; et al. (Frontiers in Immunology, 2017)
The interleukin (IL)-1 family member IL-33 has been described as intracellular alarmin with broad roles in wound healing, skin inflammation but also autoimmunity. Its dichotomy between full length (fl) IL-33 and the mature (m) form of IL-33 and its release by necrosis is still not fully understood. Here, we compare functional consequences of both forms in the skin in vivo, and therefore generated two lines of transgenic mice which selectively overexpress mmIL-33 and flmIL-33 in basal keratinocytes. Transgene mRNA was expressed at high level in skin of both lines but not in organs due to the specific K14 promoter. We could demonstrate that transgenic overexpression of mmIL-33 in murine keratinocytes leads to a spontaneous skin inflammation as opposed to flmIL-33. K14-mmIL-33 mice synthesize and secrete high amounts of mmIL-33 along with massive cutaneous manifestations, like increased epidermis and dermis thickness, infiltration of mast cells in the epidermis and dermis layers and marked hyperkeratosis. Using skin inflammation models such as IL-23 administration, imiquimod treatment, or mechanical irritation did not lead to exacerbated inflammation in the K14-flmIL-33 strain. As radiation induces a strong dermatitis due to apoptosis and necrosis, we determined the effect of fractionated radiation (12 Gy, 4 times). In comparison to wild-type mice, an increase in ear thickness in flmIL-33 transgenic mice was observed 25 days after irradiation. Macroscopic examination showed more severe skin symptoms in irradiated ears compared to controls. In summary, secreted mmIL-33 itself has a potent capacity in skin inflammation whereas fl IL-33 is limited due to its intracellular retention. During tissue damage, fl IL-33 exacerbated radiation-induced skin reaction.
EVALuna2:13432

High frequency of autoantibody-secreting cells and long-lived plasma cells within inflamed kidneys of NZB/W F1 lupus mice - Starke, Charlotte; Frey, Silke; Wellmann, Ute; Urbonaviciute, Vilma; Herrmann, Martin; Amann, Kerstin Ute; Schett, Georg; Winkler, Thomas; Voll, Reinhard E. (European Journal of Immunology, 2011)
Autoantibodies to double-stranded (ds) DNA represent a serological hallmark of systemic lupus erythematosus (SLE) and may critically contribute to the pathogenesis of lupus nephritis. Self-reactive antibodies might be partially produced by long-lived plasma cells (PCs), which mainly reside within the bone marrow and spleen. In contrast to short-lived PCs, long-lived PCs are extremely resistant to therapy and may sustain refractory disease courses. Recently, antibody-secreting cells were found within the inflamed kidneys of New Zealand black/white (NZB/W) F1 lupus mice as well as of patients with SLE. To analyze the longevity of the IgG-producing cells present in nephritic kidneys of NZB/W F1 mice we performed in vivo BrdU-labeling. We identified a higher frequency of long-lived than short-lived renal PCs, indicating that survival niches for long-lived PCs also exist within inflamed kidneys. Using ELISPOT assays, we found that on average 31% of renal IgG-producing cells reacted with dsDNA and 24% with nucleolin. Moreover, the frequencies of IgG-secreting cells specific for the autoantigens dsDNA and nucleolin were higher in the kidneys compared with those in the spleen and bone marrow.
Keywords: Autoantibody-secreting cells; Autoimmunity; Long-lived plasma cells; Lupus nephritis

Importance of the PD-1/PD-L1 Axis for Malignant Transformation and Risk Assessment of Oral Leukoplakia - Ries, Jutta; Agaimy, Abbas; Wehrhan, Falk; Baran, Christoph; Bolze, Stella; Danzer, Eva; Frey, Silke; Jantsch, Jonathan; Möst, Tobias; Büttner-Herold, Maike; Wickenhauser, Claudia; Kesting, Marco Rainer; et al. (Biomedicines, 2021)
Background: The programmed cell death ligand 1/programmed cell death receptor 1 (PD-L1/PD-1) Immune Checkpoint is an important modulator of the immune response. Overexpression of the receptor and its ligands is involved in immunosuppression and the failure of an immune response against tumor cells. PD-1/PD-L1 overexpression in oral squamous cell carcinoma (OSCC) compared to healthy oral mucosa (NOM) has already been demonstrated. However, little is known about its expression in oral precancerous lesions like oral leukoplakia (OLP). The aim of the study was to investigate whether an increased expression of PD-1/PD-L1 already exists in OLP and whether it is associated with malignant transformation. Material and Methods: PD-1 and PD-L1 expression was immunohistologically analyzed separately in the epithelium (E) and the subepithelium (S) of OLP that had undergone malignant transformation within 5 years (T-OLP), in OLP without malignant transformation (N-OLP), in corresponding OSCC and in NOM. Additionally, RT-qPCR analysis for PD-L1 expression was done in the entire tissues. Additionally, the association between overexpression and malignant transformation, dysplasia and inflammation were examined. Results: Compared to N-OLP, there were increased levels of PD-1 protein in the epithelial and subepithelial layers of T-OLP (PE = 0.001; PS = 0.005). There was no significant difference in PD-L1 mRNA expression between T-OLP and N-OLP (p = 0.128), but the fold-change increase between these groups was significant (Relative Quantification (RQ) = 3.1). In contrast to N-OLP, the PD-L1 protein levels were significantly increased in the epithelial layers of T-OLP (p = 0.007), but not in its subepithelial layers (p = 0.25). Importantly, increased PD-L1 levels were significantly associated to malignant transformation within 5 years. Conclusion: Increased levels of PD-1 and PD-L1 are related to malignant transformation in OLP and may represent a promising prognostic indicator to determine the risk of malignant progression of OLP. Increased PD-L1 levels might establish an immunosuppressive microenvironment, which could favor immune escape and thereby contribute to malignant transformation. Hence, checkpoint inhibitors could counteract tumor development in OLP and may serve as efficient therapeutic strategy in patients with high-risk precancerous lesions.
CRIS-Team WoS Importer:2021-03-19

Interleukin-36 receptor mediates the crosstalk between plasma cells and synovial fibroblasts - Schmitt, Verena; Hahn, Madelaine; Kästele, Verena; Wagner, Olga; Wiendl, Maximilian; Derer, Anja; Taddeo, Adriano; Hahne, Stefanie; Radbruch, Andreas; Jäck, Hans-Martin; Schuh, Wolfgang; Mielenz, Dirk; et al. (European Journal of Immunology, 2017)
The IL-1 family member IL-36? has proinflammatory and pathogenic properties in psoriasis. IL-36? binds to the IL-36 receptor leading to nuclear factor kappa B/mitogen activated protein kinase mediated cytokine release. The IL-36R antagonist prevents recruitment of IL-1 receptor accessory protein and therefore IL-36-dependent cell activation. In inflamed human tissue, we previously could show that resident B cells and plasma cells (PC) express IL-36?. Further, fibroblast-like synoviocytes (FLS) produced proinflammatory cytokines upon IL-36?-stimulation. We hypothesize an IL-36-specific crosstalk between B cells/PCs and FLS permitting a proinflammatory B cell niche. Here, we firstly demonstrated that B cell lines and B cells from healthy donors express IL-36? and stimulation increased IL-36? in B cells and primary plasmablasts/PCs. Moreover, FLS respond specifically to IL-36? by proliferation and production of matrix metalloproteinases via p38/HSP27 signaling. Importantly, IL-36R-deficiency abrogated IL-36?-induced production of inflammatory mediators in FLS and changed the intrinsic FLS-phenotype. Using an in vitro co-culture system, we could show that IL-36R-deficient FLS had a limited capacity to support PC survival compared to wild-type FLS. Hence, we demonstrated an IL-36R-dependent crosstalk between B cells/PCs and FLS. Our data support the concept of initiation and maintenance of a proinflammatory niche by B cells in the joints. This article is protected by copyright. All rights reserved.
EVALuna2:13406

JAK inhibition increases bone mass in steady-state conditions and ameliorates pathological bone loss by stimulating osteoblast function - Adam, Susanne; Simon, Nils; Steffen, Ulrike; Andes, Fabian T.; Scholtysek, Carina; Müller, Dorothea; Weidner, Daniela; Andreev, Darja; Kleyer, Arnd; Culemann, Stephan; Hahn, Madelaine; Schett, Georg; et al. (Science Translational Medicine, 2020)
Janus kinase (JAK)-mediated cytokine signaling has emerged as an important therapeutic target for the treatment of inflammatory diseases such as rheumatoid arthritis (RA). Accordingly, JAK inhibitors compose a new class of drugs, among which tofacitinib and baricitinib have been approved for the treatment of RA. Periarticular bone erosions contribute considerably to the pathogenesis of RA. However, although the immunomodulatory aspect of JAK inhibition (JAKi) is well defined, the current knowledge of how JAKi influences bone homeostasis is limited. Here, we assessed the effects of the JAK inhibitors tofacitinib and baricitinib on bone phenotype (i) in mice during steady-state conditions or in mice with bone loss induced by (ii) estrogen-deficiency (ovariectomy) or (iii) inflammation (arthritis) to evaluate whether effects of JAKi on bone metabolism require noninflammatory/inflammatory challenge. In all three models, JAKi increased bone mass, consistent with reducing the ratio of receptor activator of NF-κB ligand/osteoprotegerin in serum. In vitro, effects of tofacitinib and baricitinib on osteoclast and osteoblast differentiation were analyzed. JAKi significantly increased osteoblast function (P < 0.05) but showed no direct effects on osteoclasts. Additionally, mRNA sequencing and ingenuity pathway analyses were performed in osteoblasts exposed to JAKi and revealed robust up-regulation of markers for osteoblast function, such as osteocalcin and Wnt signaling. The anabolic effect of JAKi was illustrated by the stabilization of β-catenin. In humans with RA, JAKi induced bone-anabolic effects as evidenced by repair of arthritic bone erosions. Results support that JAKi is a potent therapeutic tool for increasing osteoblast function and bone formation.
CRIS-Team Scopus Importer:2020-02-21

JAK-INHIBITORS TOFACITINIB AND BARICITINIB IMPROVE PATHOLOGICAL BONE LOSS IN VIVO - Adam, Susanne; Simon, Nils; Steffen, Ulrike; Harre, Nee; Andes, Fabian; Mueller, Dorothea; Culemann, Stephan; Andreev, Darja; Hahn, Madelaine; Scholtysek, Carina; Schett, Georg; Krönke, Gerhard; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-07-12

Low dose ionising radiation leads to a NF-?B dependent decreased secretion of active IL-1? by activated macrophages with a discontinuous dose-dependency - Lödermann, Barbara; Wunderlich, Roland; Frey, Silke; Schorn, Christine; Stangl, Sonja; Roedel, Franz; Keilholz, Ludwig; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (International Journal of Radiation Biology, 2012)
Therapy with low doses of ionising radiation (X-rays) exerts anti-inflammatory effects. Little is known about whether and how low doses of X-ray treatment modulate the inflammatory phenotype of macrophages, especially the secretion of Interleukin-1beta (IL-1?).Macrophages were differentiated from human THP-1 monocytes, activated with lipopolysaccharide (LPS), treated with distinct low doses of X-rays, and co-activated with monosodium urate crystals (MSU) to induce inflammasome activation. Secretion of IL-1? was analysed by an enzyme-linked immunosorbent assay (ELISA) and Western blot. Furthermore, we analysed the intracellular amounts of the serine/threonine protein kinase B (named: Akt), mitogen-activated protein kinase p38 (p38), the v-rel reticuloendotheliosis viral oncogene homolog A (RelA), and pro- and cleaved IL-1?.Low dose X-rays led to decreased secretion of active IL-1? in a manner discontinuous with dose which was most pronounced after 0.5 or 0.7 Gy. Passive release of lactate dehydrogenase (LDH) was not influenced by X-rays. The decreased secretion of IL-1? correlated with reduced translocation of RelA, being part of the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-?B) complex, into the nucleus. After 0.5 or 0.7 Gy of X-rays, the intracellular protein amounts of up (p38) and downstream molecules (Akt) of NF-?B were reduced in activated macrophages, as were the pro- and cleaved forms of IL-1?.Distinct low doses of X-rays induce an anti-inflammatory phenotype of activated macrophages by lowering the amount of secreted IL-1? in a NF-?B dependent manner.
EVALuna2:12777

Molecular and epigenetic consequences of pre- and postnatal trauma in a mouse model - Frey, Silke; Steigleder, R.; Distler, Jörg; Kratz, Oliver; Moll, Gunther; Golub, Yulia (2017)
EVALuna2:35017

Myeloperoxidase Modulates Inflammation in Generalized Pustular Psoriasis and Additional Rare Pustular Skin Diseases - Haskamp, Stefan; Bruns, Heiko; Hahn, Madelaine; Hoffmann, Markus; Gregor, Anne; Löhr, Sabine; Hahn, Jonas; Ringer, Mark; Flamann, Cindy; Frey, Benjamin; Lesner, Adam; Thiel, Christian; et al. (American Journal of Human Genetics, 2020)
Generalized pustular psoriasis (GPP) is a severe multi-systemic inflammatory disease characterized by neutrophilic pustulosis and triggered by pro-inflammatory IL-36 cytokines in skin. While 19%–41% of affected individuals harbor bi-allelic mutations in IL36RN, the genetic cause is not known in most cases. To identify and characterize new pathways involved in the pathogenesis of GPP, we performed whole-exome sequencing in 31 individuals with GPP and demonstrated effects of mutations in MPO encoding the neutrophilic enzyme myeloperoxidase (MPO). We discovered eight MPO mutations resulting in MPO -deficiency in neutrophils and monocytes. MPO mutations, primarily those resulting in complete MPO deficiency, cumulatively associated with GPP (p = 1.85E−08; OR = 6.47). The number of mutant MPO alleles significantly differed between 82 affected individuals and >4,900 control subjects (p = 1.04E−09); this effect was stronger when including IL36RN mutations (1.48E−13) and correlated with a younger age of onset (p = 0.0018). The activity of four proteases, previously implicated as activating enzymes of IL-36 precursors, correlated with MPO deficiency. Phorbol-myristate-acetate-induced formation of neutrophil extracellular traps (NETs) was reduced in affected cells (p = 0.015), and phagocytosis assays in MPO-deficient mice and human cells revealed altered neutrophil function and impaired clearance of neutrophils by monocytes (efferocytosis) allowing prolonged neutrophil persistence in inflammatory skin. MPO mutations contribute significantly to GPP's pathogenesis. We implicate MPO as an inflammatory modulator in humans that regulates protease activity and NET formation and modifies efferocytosis. Our findings indicate possible implications for the application of MPO inhibitors in cardiovascular diseases. MPO and affected pathways represent attractive targets for inducing resolution of inflammation in neutrophil-mediated skin diseases.
CRIS-Team Scopus Importer:2020-09-11
Keywords: ACH; acrodermatitis continua suppurativa Hallopeau; activation of IL-36 precursors; acute generalized 4 exanthematous pustulosis; AGEP; efferocytosis; generalized pustular psoriasis; GPP; impaired NETosis; MPO deficiency; myeloperoxidase; oligogenic inheritance

Overexpression of transmembrane TNF drives development of ectopic lymphoid structures in the bone marrow and B cell lineage alterations in experimental spondyloarthritis - Kaaij, Merlijn H.; Rip, Jasper; Jeucken, Kim C.M.; Kan, Yik Y.; van Rooijen, Charlotte C.N.; Saris, Job; Pots, Desiree; Frey, Silke; Grootjans, Joep; Schett, Georg; van Duivenvoorde, Leonie M.; Nolte, Martijn A.; et al. (Journal of Immunology, 2021)
TNF is important in immune-mediated inflammatory diseases, including spondyloarthritis (SpA). Transgenic (tg) mice overexpressing transmembrane TNF (tmTNF) develop features resembling human SpA. Furthermore, both tmTNF tg mice and SpA patients develop ectopic lymphoid aggregates, but it is unclear whether these contribute to pathology. Therefore, we characterized the lymphoid aggregates in detail and studied potential alterations in the B and T cell lineage in tmTNF tg mice. Lymphoid aggregates developed in bone marrow (BM) of vertebrae and near the ankle joints prior to the first SpA features and displayed characteristics of ectopic lymphoid structures (ELS) including presence of B cells, T cells, germinal centers, and high endothelial venules. Detailed flow cytometric analyses demonstrated more germinal center B cells with increased CD80 and CD86 expression, along with significantly more T follicular helper, T follicular regulatory, and T regulatory cells in tmTNF tg BM compared with non-tg controls. Furthermore, tmTNF tg mice exhibited increased IgA serum levels and significantly more IgA+ plasma cells in the BM, whereas IgA+ plasma cells in the gut were not significantly increased. In tmTNF tg 3 TNF-RI2/2 mice, ELS were absent, consistent with reduced disease symptoms, whereas in tmTNF tg 3 TNF-RII2/2 mice, ELS and clinical symptoms were still present. Collectively, these data show that tmTNF overexpression in mice results in osteitis and ELS formation in BM, which may account for the increased serum IgA levels that are also observed in human SpA. These effects are mainly dependent on TNF-RI signaling and may underlie important aspects of SpA pathology.
CRIS-Team Scopus Importer:2021-11-12

Prenatal Alcohol Exposure Is Associated With Adverse Cognitive Effects and Distinct Whole-Genome DNA Methylation Patterns in Primary School Children - Frey, Silke; Eichler, Anna; Stonawski, Valeska; Kriebel, Jennifer; Wahl, Simone; Gallati, Sabina; Goecke, Tamme W.; Fasching, Peter A.; Beckmann, Matthias W.; Kratz, Oliver; Moll, Gunther; Heinrich, Hartmut; et al. (Frontiers in Behavioral Neuroscience, 2018)
Prenatal alcohol exposure (PAE) is known to elicit a broad range of systemic effects, including neurophysiological alterations that result in adverse behavioral and cognitive outcomes. However, molecular pathways underlying these long-term intrauterine effects remain to be investigated. Here, we tested a hypothesis that PAE may lead to epigenetic alterations to the DNA resulting in attentional and cognitive alterations of the children. We report the results of the study that included 156 primary school children of the Franconian Cognition and Emotion Studies (FRANCES) cohort which were tested for an objective marker of PAE, ethyl glucuronide (EtG) in meconium at birth. Thirty-two newborns were found to be exposed to alcohol with EtG values above 30 ng/g (EtG+). Previously we described PAE being associated with lower IQ and smaller amplitude of the event-related potential component P3 in go trials (Go-P3), which indicates a reduced capacity of attentional resources. Whole-genome methylation analysis of the buccal cell DNA revealed 193 differentially methylated genes in children with positive meconium EtG, that were clustered into groups involved in epigenetic modifications, neurodegeneration, neurodevelopment, axon guidance and neuronal excitability. Furthermore, we detected mediation effects of the methylation changes in DPP10 and SLC16A9 genes on the EtG related cognitive and attention-related deficits. Our results suggest that system-wide epigenetic changes are involved in long-term effects of PAE. In particular, we show an epigenetic mediation of PAE effects on cognition and attention-related processes.
EVALuna2:36368

Rare frameshift mutation in SERPINA3 contributes to generalized pustular psoriasis - Hüffmeier, Ulrike; Sticht, Heinrich; Wenzel, J.; Wilsmann-Theis, D.; Wolff, K.; Löhr, Sabine; Frey, Benjamin; Hahn, M.; Ekici, Arif Bülent; Uebe, S.; Thiel, Christian; Wiesmann da Silva Reis, André; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Rare Loss-of-Function Mutation in SERPINA3 in Generalized Pustular Psoriasis - Frey, Silke; Sticht, Heinrich; Wilsmann-Theis, Dagmar; Gerschütz, Anne; Wolf, Katharina; Löhr, Sabine; Haskamp, Stefan; Frey, Benjamin; Hahn, Madelaine; Ekici, Arif Bülent; Uebe, Steffen; Thiel, Christian; et al. (Journal of Investigative Dermatology, 2020)
CRIS-Team Scopus Importer:2020-03-06

Structural insights into heme binding to IL-36α proinflammatory cytokine - Wißbrock, Amelie; Goradia, Nishit B.; Kumar, Amit; Paul George, Ajay Abisheck; Kühl, Toni; Bellstedt, Peter; Ramachandran, Ramadurai; Hoffmann, Patrick; Galler, Kerstin; Popp, Jürgen; Neugebauer, Ute; Hampel, Kornelia; et al. (Scientific Reports, 2019)
Cytokines of the interleukin (IL)-1 family regulate immune and inflammatory responses. The recently discovered IL-36 family members are involved in psoriasis, rheumatoid arthritis, and pulmonary diseases. Here, we show that IL-36α interacts with heme thereby contributing to its regulation. Based on in-depth spectroscopic analyses, we describe two heme-binding sites in IL-36α that associate with heme in a pentacoordinated fashion. Solution NMR analysis reveals structural features of IL-36α and its complex with heme. Structural investigation of a truncated IL-36α supports the notion that the N-terminus is necessary for association with its cognate receptor. Consistent with our structural studies, IL-36-mediated signal transduction was negatively regulated by heme in synovial fibroblast-like synoviocytes from rheumatoid arthritis patients. Taken together, our results provide a structural framework for heme-binding proteins and add IL-1 cytokines to the group of potentially heme-regulated proteins.
CRIS-Team Scopus Importer:2019-11-26

The complement system drives local inflammatory tissue priming by metabolic reprogramming of synovial fibroblasts - Friščić, Jasna; Böttcher, Martin; Reinwald, Christiane; Bruns, Heiko; Wirth, Benjamin; Popp, Sebastian; Walker, Kellie Irene; Ackermann, Jochen A.; Chen, Xi; Turner, Jason; Zhu, Honglin; Seyler, Lisa; et al. (Immunity, 2021)
Arthritis typically involves recurrence and progressive worsening at specific predilection sites, but the checkpoints between remission and persistence remain unknown. Here, we defined the molecular and cellular mechanisms of this inflammation-mediated tissue priming. Re-exposure to inflammatory stimuli caused aggravated arthritis in rodent models. Tissue priming developed locally and independently of adaptive immunity. Repeatedly stimulated primed synovial fibroblasts (SFs) exhibited enhanced metabolic activity inducing functional changes with intensified migration, invasiveness and osteoclastogenesis. Meanwhile, human SF from patients with established arthritis displayed a similar primed phenotype. Transcriptomic and epigenomic analyses as well as genetic and pharmacological targeting demonstrated that inflammatory tissue priming relies on intracellular complement C3- and C3a receptor-activation and downstream mammalian target of rapamycin- and hypoxia-inducible factor 1α-mediated metabolic SF invigoration that prevents activation-induced senescence, enhances NLRP3 inflammasome activity, and in consequence sensitizes tissue for inflammation. Our study suggests possibilities for therapeutic intervention abrogating tissue priming without immunosuppression.
CRIS-Team Scopus Importer:2021-04-19
Keywords: arthritis; cell metabolism; cellular senescence; complement system; inflammasome; inflammation; mechanistic target of rapamycin; synovial fibroblasts; tissue priming; trained immunity

The genetic basis for most patients with pustular skin disease remains elusive - Mössner, R.; Wilsmann-Theis, D.; Oji, V.; Gkogkolou, P.; Löhr, S.; Schulz, P.; Körber, A.; Prinz, J. C.; Renner, R.; Schäkel, K.; Vogelsang, L.; Peters, K. P.; et al. (British Journal of Dermatology, 2017)
Rare variants in the genes IL36RN, CARD14 and AP1S3 have been identified to cause/ contribute to pustular skin diseases, primarily generalized pustular psoriasis (GPP).To better understand the disease-relevance of these genes, we screened our cohorts of patients with pustular skin diseases (primarily GPP and palmoplantar pustular psoriasis [PPP]) for coding changes in these three genes. Carriers of single heterozygous IL36RN mutations were screened for a second mutation in IL36RN.Coding exons of IL36RN, CARD14 and AP1S3 were sequenced in 67 patients - 61 with GPP, 2 with acute generalized exanthematous pustulosis and 4 with acrodermatitis continua suppurativa Hallopeau. We screened IL36RN and AP1S3 for intragenic copy-number-variants, 258 PPP patients for coding changes in AP1S3. 11 heterozygous IL36RN mutations carriers were analyzed for a 2(nd) non-coding IL36RN mutation. Genotype-phenotype-correlations in carriers/ non-carriers of IL36RN mutations were assessed within the GPP cohort.The majority of patients (GPP:64%) did not carry rare variants in any of the three genes. Bi-allelic and mono-allelic IL36RN mutations were identified in 15 and 5 GPP patients, respectively. Non-coding rare IL36RN variants were not identified in heterozygous carriers. The only significant genotype-phenotype-correlation observed for IL36RN mutation carriers was early age of disease onset. Additional rare CARD14 or AP1S3 variants were identified in 15% of IL36RN mutations carriers.The identification of IL36RN mutation carriers harboring additional rare variants in CARD14 or AP1S3, indicates a more complex mode of inheritance of pustular psoriasis. Our results suggest additional disease-causing genetic factors in heterozygous IL36RN mutation carriers outside IL36RN. This article is protected by copyright. All rights reserved.
EVALuna2:9330

The human sialic acid-binding immunoglobulin-like lectin Siglec-9 and its murine homolog Siglec-E control osteoclast activity and bone resorption - Andes, F. T.; Adam, Susanne; Hahn, Madelaine; Aust, O.; Frey, Silke; Grüneboom, Anika; Nitschke, Lars; Schett, Georg; Steffen, Ulrike (Bone, 2020)
Regulation of osteoclast differentiation and function is a central element in bone homeostasis. While the role of soluble factors, such as cytokines, hormones and growth factors, in controlling osteoclast differentiation has been intensively characterized, the function of surface receptors is less well understood. Sialic acid-binding immunoglobulin-like lectin (Siglec)-9 and its murine homolog Siglec-E are sialic acid-recognizing inhibitory receptors from the CD33-related Siglec-family and mainly expressed on myeloid cells. We found Siglec-9 and Siglec-E to be expressed at all stages of human and murine osteoclastogenesis, respectively. Siglec-E knockout mice displayed lower bone mass despite unchanged osteoclast numbers and an increased bone formation rate. Ex vivo osteoclast assays using Siglec-E knockout cells or a blocking antibody against human Siglec-9 confirmed the suppressive effect of Siglec-9/Siglec-E on osteoclast function. Although osteoclast numbers were unchanged or even slightly decreased, the blockade/absence of Siglec-9/Siglec-E resulted in an augmented resorption activity of mature osteoclasts. This increased resorption activity was associated with enlarged actin rings. Together, our results suggest Siglec-9/Siglec-E to inhibit osteoclast activation independently from osteoclast differentiation and thereby propose a new mechanism for the control of local bone resorption.
CRIS-Team Scopus Importer:2020-10-16
Keywords: Bone; Osteoclasts; Resorption; Siglec-9; Siglec-E

The soluble CD83 protein prevents bone destruction by inhibiting the formation of osteoclasts and inducing resolution of inflammation in arthritis - Royzman, Dmytro; Andreev, Darja; Stich, Lena; Peckert, Katrin; Wild, Andreas; Zinser, Elisabeth; Mühl-Zürbes, Petra; Jones, Evan; Adam, Susanne; Frey, Silke; Fuchs, Maximilian; Kunz, Meik; et al. (Frontiers in Immunology, 2022)
Here we show that soluble CD83 induces the resolution of inflammation in an antigen-induced arthritis (AIA) model. Joint swelling and the arthritis-related expression levels of IL-1 beta, IL-6, RANKL, MMP9, and OC-Stamp were strongly reduced, while Foxp3 was induced. In addition, we observed a significant inhibition of TRAP(+) osteoclast formation, correlating with the reduced arthritic disease score. In contrast, cell-specific deletion of CD83 in human and murine precursor cells resulted in an enhanced formation of mature osteoclasts. RNA sequencing analyses, comparing sCD83- with mock treated cells, revealed a strong downregulation of osteoclastogenic factors, such as Oc-Stamp, Mmp9 and Nfatc1, Ctsk, and Trap. Concomitantly, transcripts typical for pro-resolving macrophages, e.g., Mrc1/2, Marco, Klf4, and Mertk, were upregulated. Interestingly, members of the metallothionein (MT) family, which have been associated with a reduced arthritic disease severity, were also highly induced by sCD83 in samples derived from RA patients. Finally, we elucidated the sCD83-induced signaling cascade downstream to its binding to the Toll-like receptor 4/(TLR4/MD2) receptor complex using CRISPR/Cas9-induced knockdowns of TLR4/MyD88/TRIF and MTs, revealing that sCD83 acts via the TRIF-signaling cascade. In conclusion, sCD83 represents a promising therapeutic approach to induce the resolution of inflammation and to prevent bone erosion in autoimmune arthritis.
CRIS-Team WoS Importer:2022-09-09

Zoledronate causes a systemic shift of macrophage polarization towards M1 in vivo - Weber, Manuel; Homm, Andi; Müller, Stefan; Frey, Silke; Amann, Kerstin Ute; Ries, Jutta; Geppert, Carol-Immanuel; Preidl, Raimund; Möst, Tobias; Kämmerer, Peer W.; Kesting, Marco Rainer; Wehrhan, Falk (International Journal of Molecular Sciences, 2021)
Background: Immunomodulatory properties of bisphosphonates (BP) are suggested to contribute to the development of medication‐associated osteonecrosis of the jaw (MRONJ). Further-more, bisphosphonate‐derived immune modulation might contribute to the anti‐metastatic effect observed in breast cancer patients. Macrophages are potential candidates for the mediation of immunomodulatory effects of bisphosphonates. The study aimed to investigate the influence of bisphosphonates alone and in combination with surgical trauma on systemic macrophage polarization (M1 vs. M2) using an in vivo rat model. Methods: A total of 120 animals were divided into four groups. Groups 2 and 4 were treated with 8 × 40 μg/kg body weight of the BP Zoledronate i.p. (week 0–7). Groups 3 and 4 were exposed to surgical trauma (week 8, tooth extraction + tibia fracture), whereas in Group 1 neither medication nor surgical trauma was applied. After 8, 10, 12 and 16 weeks, skin, lung and spleen were immunohistochemically examined for macrophage polarization via expression analysis of CD68, CD163 and iNOS using a tissue microarray (TMA). Results: A significant shift of macrophage polarization towards M1 was observed in skin, spleen and lung tissue of animals, with and without surgical trauma, treated with BP when compared to those without BP application. Surgical trauma did not cause a significant increase towards M1 polarization. Conclusions: BP application leads to a systemic pro‐inflammatory situation in vivo, independent of surgical trauma, as evidenced by the shift in macrophage polarization towards M1 in various somatic tissues. This provides a possible explanation for the clinically observed anti‐tumor effect of bisphosphonates and might also contribute to pathogenesis of MRONJ.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Antiresorptives; Bisphosphonate; Immune modulation; M1; M2; Macrophage polarization; Zoledronate